Correlated Evolution of Short Wavelength Sensitive Photoreceptor Sensitivity and Color Pattern in Lake Malawi Cichlids - Pauers, Michael J.; Kuchenbecker, James A.; Joneson, Suzanne L.; Neitz, Jay (Frontiers in Ecology and Evolution, 2016)
For evolutionary ecologists, the “holy grail” of visual ecology is to establish an unambiguous link between photoreceptor sensitivity, the spectral environment, and the perception of specific visual stimuli (e.g., mates, food, predators, etc.). Due to the bright nuptial colors of the males, and the role female mate choice plays in their evolution, the haplochromine cichlid fishes of the African great lakes are favorite research subjects for such investigations. Despite this attention, current evidence is equivocal; while distinct correlations among photoreceptor sensitivity, photic environment, and male coloration exist in Lake Victorian haplochromines, attempts to find such correlations in Lake Malawian cichlids have failed. Lake Malawi haplochromines have a wide variability in their short-wavelength-sensitive photoreceptors, especially compared to their mid- and long-wavelength-sensitive photoreceptors; these cichlids also vary in the degree to which they express one of three basic color patterns (vertical bars, horizontal stripes, and solid patches of colors), each of which is likely used in a different form of communication. Thus, we hypothesize that, in these fishes, spectral sensitivity and color pattern have evolved in a correlated fashion to maximize visual communication; specifically, ultraviolet sensitivity should be found in vertically-barred species to promote ‘private’ communication, while striped species should be less likely to have ultraviolet sensitivity, since their color pattern carries ‘public’ information. Using phylogenetic independent contrasts, we found that barred species had strong sensitivity to ultraviolet wavelengths, but that striped species typically lacked sensitivity to ultraviolet light. Further, the only variable, even when environmental variables were simultaneously considered, that could predict ultraviolet sensitivity was color pattern. We also found that, using models of correlated evolution, color pattern and ultraviolet sensitivity are correlated in Lake Malawi cichlid evolution, with the likely ancestor being a vertically-barred, ultraviolet-sensitive species, the descendants of which lost both ultraviolet sensitivity and a barred color pattern. These results, indicating that communication of ‘public’ and ‘private’ signals is mediated via differing perceptions of color patterns, suggest a functional connection between visual sensitivity and colour pattern, a novel finding in Lake Malawi cichlids.